Effect of a stewardship intervention on adherence to uncomplicated cystitis and pyelonephritis guidelines in an emergency department setting. - Michelle T Hecker (Public Library of Science (PLoS), 2014)
Objective To evaluate adherence to uncomplicated urinary tract infections (UTI) guidelines and UTI diagnostic accuracy in an emergency department (ED) setting before and after implementation of an antimicrobial stewardship intervention. Methods The intervention included implementation of an electronic UTI order set followed by a 2 month period of audit and feedback. For women age 18-65 with a UTI diagnosis seen in the ED with no structural or functional abnormalities of the urinary system, we evaluated adherence to guidelines, antimicrobial use, and diagnostic accuracy at baseline, after implementation of the order set (period 1), and after audit and feedback (period 2). Results Adherence to UTI guidelines increased from 44% (baseline) to 68% (period 1) to 82% (period 2) (P≤.015 for each successive period). Prescription of fluoroquinolones for uncomplicated cystitis decreased from 44% (baseline) to 14% (period 1) to 13% (period 2) (P<.001 and P = .7 for each successive period). Unnecessary antibiotic days for the 200 patients evaluated in each period decreased from 250 days to 119 days to 52 days (P<.001 for each successive period). For 40% to 42% of cases diagnosed as UTI by clinicians, the diagnosis was deemed unlikely or rejected with no difference between the baseline and intervention periods. Conclusions A stewardship intervention including an electronic order set and audit and feedback was associated with increased adherence to uncomplicated UTI guidelines and reductions in unnecessary antibiotic therapy and fluoroquinolone therapy for cystitis. Many diagnoses were rejected or deemed unlikely, suggesting a need for studies to improve diagnostic accuracy for UTI.